2021
DOI: 10.1016/j.repbio.2021.100559
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the cross-talk between mediators of infertility and COVID-19

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 150 publications
1
25
1
7
Order By: Relevance
“…The question of a possible passage of SARS-CoV-2 in the sperm is still debated. The expression of ACE-2, TMPRSS2, and CD147 receptors in the testes, epididymis, prostrate and seminal vesicles has been reported [29], which support the hypothesis of a potential entry of the SARS-CoV-2. Moreover, in the testes, epididymis and seminal vesicles, the expression of lysosomal cathepsins (CTSB/CTSL) and/ neuropilin-1 (NRP-1) which also promote viral invasion…”
Section: Plos Onesupporting
confidence: 64%
“…The question of a possible passage of SARS-CoV-2 in the sperm is still debated. The expression of ACE-2, TMPRSS2, and CD147 receptors in the testes, epididymis, prostrate and seminal vesicles has been reported [29], which support the hypothesis of a potential entry of the SARS-CoV-2. Moreover, in the testes, epididymis and seminal vesicles, the expression of lysosomal cathepsins (CTSB/CTSL) and/ neuropilin-1 (NRP-1) which also promote viral invasion…”
Section: Plos Onesupporting
confidence: 64%
“…According to the literature, these are the tissues most targeted by Covid-19b [ 84 ]. In this regard, recent studies have demonstrated the high expression of ACE2 and TMPRSS2 receptors in spermatogonia, Sertoli and Leydig cells and in male accessory organs such as prostate, seminal vesicles and bulbourethral glands [ 85 88 ]. In an original study, when semen parameters and serum testosterone level were assessed after diagnosis of COVID-19, mean semen volume, sperm motility, normal sperm morphology and serum testosterone were found to be significantly decreased.…”
Section: Methodsmentioning
confidence: 99%
“…Complex inflammatory infiltration can cause extensive destruction of germ cells and spermatids [57]. Due to hyperactivation of the human immune system after COVID-19, the virus infection can lead to cytokine storms under strong immune stimulus, thus making damage to multiple organs in the body, including the testis [58]. In addition, fever, hypoxia, and mental stress during COVID-19 are also important factors impairing male fertility and sperm quality [21].…”
Section: Discussionmentioning
confidence: 99%